The parliamentary debate devoted to the project of the marriage law of 1818 as the plane of exchange of political and legal ideas - Kania, Rafał (The Opole Studies in Administration and Law, 2016)
Contemporary research concept of the history of political and legal thought includes various sources of information about opinions on politics, state and law that appeared in the past. One of them is a parliamentary debate. The article concentrates on the discussion about the marriage law that took place in the Polish Parliament (Sejm) in 1818. At that time one of the most controversial law institutions was the divorce. The legislative bill divided Members of Parliament into three different groups. The first party supported the project of the new matrimonial law that was prepared by the government (The Council of State). The second group considered acceptance of the religious norms that were given by the Roman Catholic Church to be the most appropriate solution. The last one was formed by liberals who opposed voting in favour of the project, which – in their opinion – extremely invaded human privacy and freedom. The content of the debate also presents three major conceptions of the system of government that prevailed in the Kingdom of Poland.